PENGARUH METODE PEMBELAJARAN PROBLEM SOLVING DAN THINK PAIR SHARE DENGAN MENGGUNAKAN MEDIA POWER POINT TERHADAP PRESTASI BELAJAR SISWAN DI SMP NEGERI 1 GUBUG TAHUN PELAJARAN 2012/2013 - Ismiyati Ismiyati; Joko Siswanto; Nur Khoiri (Jurnal Penelitian Pembelajaran Fisika, 2013)
Purpose of this study was to determine the effect of differences in learning achievement of physics that uses methods of Problem Solving and Think Pair Share with media power point on student achievement SMP N 1 Gubug School Year 2012/2013. This research is an experimental study conducted in class VIII in the country SMP N 1 Gubug. Population in this study were all students of class VIII. Selected by Cluster Random Sampling is 3 classes as the experimental class VIII A as the experimental class 1, VIII B as the experimental class 2, class VIII C as a control. Data retrieval is done using tests and documentation. This study uses a single track obtained anava Fhitung > Ftable is 8.656> 3.079 thus Ho is rejected, it can be concluded therefore think pair share learning with media power point is more effective than learning problem solving with power point and conventional media in the country SMP N 1 Gubug school year 2012/2013